Molecular genetics of naringenin biosynthesis, a typical plant secondary metabolite produced by Streptomyces clavuligerus. Issue 1 (December 2015) - Álvarez-Álvarez, Rubén; Botas, Alma; Albillos, Silvia; Rumbero, Angel; Martín, Juan; Liras, Paloma
Abstract Background Some types of flavonoid intermediates seemed to be restricted to plants. Naringenin is a typical plant metabolite, that has never been reported to be produced in prokariotes. Naringenin is formed by the action of a chalcone synthase using as starter 4-coumaroyl-CoA, which in dicotyledonous plants derives from phenylalanine by the action of a phenylalanine ammonia lyase. Results A compound produced byStreptomyces clavuligerus has been identified by LC–MS and NMR as naringenin and coelutes in HPLC with a naringenin standard. Genome mining ofS. clavuligerus revealed the presence of a gene for a chalcone synthase (ncs ), side by side to a gene encoding a P450 cytochrome (ncyP ) and separated from a gene encoding a Pal/Tal ammonia lyase (tal ). Deletion of any of these genes results in naringenin non producer mutants. Complementation with the deleted gene restores naringenin production in the transformants. Furthermore, naringenin production increases in cultures supplemented with phenylalanine or tyrosine. Conclusion This is the first time that naringenin is reported to be produced naturally in a prokariote. Interestingly three non-clustered genes are involved in naringenin production, which is unusual for secondary metabolites. A tentative pathway for naringenin biosynthesis has been proposed.